Manajemen Peserta Didik Berbasis Pesantren dalam Mewujudkan Karakter Pelajar Pancasila - Anggraini, Helda Yusfarina; Zamroni, Zamroni (El-Idare, 2024)
The current Pancasila student character program is being promoted as an effort to recover from the crisis of students' character. The presence of student management based on Islamic boarding schools is expected to assist students in achieving the values ​​contained in the Pancasila student character. The purpose of this research is to analyze and describe student management based on Islamic boarding schools in realizing the Pancasila student character at SMA Madina Citra Insani Samarinda. The research uses a qualitative descriptive method with data collection through interviews, observations, and documentation. The Miles, Huberman, and Saldana model is used to analyze the data found. The research findings on student management based on Islamic boarding schools in realizing the Pancasila student character begin with the stages: (1) planning, including the determination of character values, socialization, and the arrangement of daily programs; (2) organizing, including the arrangement of the school's organizational structure; (3) implementation, including formal and non-formal education, organizations, and extracurricular activities; (4) supervision by the school principal and the pesantren's astidz. Meanwhile, the program activities include the analysis of student needs (AKPD), new student admissions (PPDB), selection, school environmental introduction period (MPLS), placement and specialization of students, development and guidance of students, reporting on students, as well as graduation and alumni.